Ukrainian national traditions of children and youth education in the family - Mykhaylyshyn, Romana (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2014)
Ukrainian people’s family traditions in the education of children and youths in thenational revival of education in Ukraine is particularly acutely needed to renew traditionalUkrainian family education as a source of the spiritual and moral formation ofnational consciousness, establishing norms and values of the Ukrainian mentality. Family education is an important part of the educational process. In Ukraine, it hasdeep historical roots, as the experience accumulated since ancient times. Family educationbased on the national identity is a historical educational system of beliefs, idealsand generation link effects on children and young people, designed to create a moraland aesthetic identity, to ensure the development of spiritual unity and the heritage ofgenerations.
Keywords: family; traditions; customs; rites; folk wisdom; family pedagogy